Lymphedema during pregnancy - case study - Korabiusz, Katarzyna; Wawrykow, Agata; Torbe, Dorota; Torbe, Andrzej (Journal of Education, Health and Sport, 2017)
Pregnancy is a period when woman’s body undergoes a lot of changes in her hormonal balance, lymphatic system, musculoskeletal system and cardiovascular system. As a result of disorders in defense mechanisms, a significant amount of liquid accumulates in spaces between tissues. A clinical manifestation of this condition is swelling located around ankles and lower legs. Sedentary lifestyle, unhealthy eating habits, excessive weight and pregnancy are also well known causes of lymphatic swelling. Comprehensive anti-swelling therapy that is used in treating lymphatic swelling in pregnant patients includes: patients’ education, manual lymphatic drainage, kinesitherapy, multilayer bandaging, skin care, drainage positions and kinesiotaping. Dissertation’s objective: Dissertation’s objective is to evaluate implementation of manual lymphatic drainage and anti-swelling kinesiotaping in pregnant woman with lymphatic swelling of lower legs. Research methods: Research methods were collected basing on: interview with a patient, medical documentation analysis and physical examination conduced before and after therapy. Research was conducted between 34th and 36th week of pregnancy. Case study: 38 year old patient in her fourth singleton pregnancy. Two prior pregnancies in 2009 and 2010 were delivered with C-section and one missed abortion in 2015 occurred. During this pregnancy patient gained over 30kg. She was diagnosed with lymphatic swelling of metatarsus, lower legs and ankles in 34th week of pregnancy. Lymphatic drainage of lower limbs and anti-swelling kinesiotaping was implemented. Results: After two weeks of therapy decrease in swelling was observed in left lower limb: in metatarsus by 8cm, in ankles by 9cm and in lower legs by 6cm. In right lower limb swelling decreased accordingly by 7cm, 10cm and 5cm. Conclusion: Anti-swelling lymphatic drainage, kinesiotherapy and kinesiotaping are effective physiotherapy methods used in treating lymphedema in pregnant women.